MARKETING STRATEGY OF ORNAMENTAL PLANTS IN MUARA BANGKAHULU DISTRICT, BENGKULU (CASE STUDY AT KARYA TAMAN FLOWER DEPOT) - Oktaviani, Anggita Dwi; Mulyasari, Gita; Irnad (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
Ornamental plants are now an essential element in beautifying companies, housing, city parks, and certain areas, thereby increasing demand in the future. The success of ornamental plant agribusiness is influenced by marketing strategies, which often follow trends. When a trend occurs, the price of ornamental plants soars, but decreases when a new trend appears. Ornamental plants are also not a basic necessity consumed every day, so it is necessary to develop the most appropriate marketing strategy to achieve the desired business turnover and reach a wider market share. The data analysis used in assessing these objectives is IFAS, EFAS, I-E Matrix, SWOT Analysis, and QSPM analysis. The research results show that the IFE (3.126) and EFE (3.35) values ​​are above 3, indicating a strong flower depot business environment. Karya Taman Flower Depot can exploit its strengths and opportunities to minimize the impact of existing weaknesses and threats. IE matrix mapping is in cell division I, namely the growth and build stage. SWOT analysis produces eight alternative strategies. The priority strategy based on QSPM is to expand the market by utilizing technological developments, improve management functions by increasing the number of employees, become the leading supplier of greening needs in housing complexes, offices, and other agencies, and carry out more intensive promotions.